(untitled) (International Journal of Nursing Education, 2020)
Teaching and learning are two important components that travel synchronously in the journey of education.It is also like two sides of a coin that is used in our day-to-day life. Current students need newer andinteractive method of learning. Gallery walk is an active learning approach performed in the classroom,which facilitates students to gain knowledge on a specific subject matter through interaction. The main aimof this active learning experience is to share experience of the Gallery walk as classroom interactive learningmethod: Nurse Educators’ Reflection. The scope is to stimulate critical thinking amongst students that enrichthe teaching learning environment in an optimistic fashion. A trial implementation of gallery walk was donein the nursing classroom of Symbiosis CON during a child health nursing lecture by the second author. Theinstructor gave the basic guidelines about the gallery walk. Every student passed through the six tables,which had a discussion period of 15 minutes each. After all groups finish with all study tables, the instructoror facilitator gathered the class and summarized the topic. The collective reflections from students willbe used for the betterment of this method for future lectures. This paper focuses on the nurse educator’sperspectives beginning from planning, implementing and evaluating the Gallery walk as a classroom basedactive learning approach in a nursing college. To conclude, synchronized learning environment is essentialfor all the undergraduate nursing students in all levels of learning.